A study on approximate controllability of non-autonomous evolution system with nonlocal conditions using sequence method. (16th December 2022) - Gou, Haide; Li, Yongxiang
Abstract : The purpose of this paper is concerned with the existence of mild solutions and approximate controllability for a class of non-autonomous evolution system with nonlocal conditions in Banach spaces. First, the existence of mild solution is obtained by means of contraction mapping principle. Then sufficient conditions have been presented to establish the approximate controllability by using the sequence method. The application of the theory is explained by an example.